Danhong injection in the treatment of chronic stable angina: study protocol for a randomized controlled trial. Issue 1 (December 2015) - Wang, Peng; Li, Dan; Dong, Wei; Liu, Jun; Yu, Ya; Shen, Chun; Chen, Qi; Chen, Bing; Chen, Yun; Wang, Zhong
Abstract Background Chronic stable angina is a leading cause of death worldwide. Danhong injection, a complementary alternative medicine for chronic stable angina, has been demonstrated to be effective in numerous studies and is widely prescribed to patients. However, the methodological quality of most prior studies was found to be, in general, low. Therefore, we designed this randomized controlled trial to evaluate the efficacy and safety of using Danhong injection to treat chronic stable angina. Methods/design This is a randomized multicentre, double-blind, placebo-controlled, adaptive clinical trial. A total of 870 patients meeting the eligibility criteria will be randomly assigned into either the Danhong injection or the placebo group in a 2:1 ratio. Participants will then undergo a 2-week treatment regimen and a 76-day follow-up period. Because this is an adaptive trial, two interim analyses are prospectively planned. These will be performed after one-third and two-thirds of the patients, respectively, have completed the trial. Based on the results of these interim analyses, a data monitoring committee will determine how to modify aspects of the study without undermining the validity and integrity of the trial. The primary outcome measure is the proportion of patients who show a clinically significant change, which is defined as at least a 20-point improvement in angina frequency score on the Seattle Angina Questionnaire, which will be administered on day 30. Other secondary efficacy and safety outcomes will also be assessed. Discussion This trial will provide high-quality evidence regarding the use of Danhong injection to treat chronic stable angina. Trial registration ClinicalTrials.gov:NCT01681316 .